Analysis of Structure, Behavior and Performance of Communications Technology Industry Companies - Nyoman Ngurah Bagus Wiranata Giri; I Wayan Sukadana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The communications technology industry is a dynamic industry and is always changing along with developments in the business environment. Technology companies often learn new individual needs as quickly as possible which forces companies to innovate business models, and this industry has promising prospects because the market is getting bigger. The aim of this research is to analyze the structure, behavior and performance of companies that dominate the communications technology industry. This research uses secondary data with qualitative and quantitative approaches obtained directly through intermediary media. The sample collection method used was the non-participant observation method. Data analysis techniques use concentration ratio analysis, HHI index test, descriptive analysis. The results of this research show 1) The market structure of the communications technology industry is proven to be an oligopoly. 2) The market structure in the communications technology industry is influenced by company behavior. 3) Market structure and company behavior influence company performance. The implications of this research are that structure, behavior and performance influence each other in the communications technology industry.